1999
DOI: 10.1289/ehp.99107663
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of arsenic in urine as a function of exposure to arsenic in drinking water.

Abstract: Urinary arsenic (As) concentrations were evaluated as a biomarker of exposure in a U.S. population chronically exposed to inorganic As (InAs) in their ddnking water. Ninety-si individuals who consumed drinking water with As concentrations of 8-620 P/L provided first moring urine voids for up to 5 consecutive days. The study population was 56% male, and 44% was younger than 18 year of age. On one day of the study period, all voided urines were collected over a 24-hr period. Arsenic intake from drnking water was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(46 citation statements)
references
References 21 publications
1
40
0
5
Order By: Relevance
“…Cognitive tests that showed association with UAs represent complex cognitive processes such as memory, problem solving, and attention. Previous studies had shown an adverse relationship between As exposure and IQ (Calderon et al 1999) and neurobehavioral performance (Rodriguez et al 2003). Results from our study confirm earlier findings by Calderón et al (2001) and Tsai et al (2003) relating As exposure to memory alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive tests that showed association with UAs represent complex cognitive processes such as memory, problem solving, and attention. Previous studies had shown an adverse relationship between As exposure and IQ (Calderon et al 1999) and neurobehavioral performance (Rodriguez et al 2003). Results from our study confirm earlier findings by Calderón et al (2001) and Tsai et al (2003) relating As exposure to memory alterations.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that a moderately strong correlation exists between arsenic concentrations in single first morning samples and samples collected over 24 hours (Calderon et al 1999). Urine samples were kept frozen in field laboratories at −20° C for 2–4 weeks, then transported to the main study office in Chile for longer-term storage at −80° C. Most samples were stored frozen for one to four months before analysis.…”
Section: Methodsmentioning
confidence: 97%
“…Collection of urine for 24 hr can be difficult, because of quality assurance logistics, particularly if a large number of samples are to be collected. Urinary arsenic does not appear to vary over time, so spot collection or first morning void may be used (Calderon et al 1999; Hewitt et al 1995). In addition, intraindividual variation of iAs metabolism and its urinary excretion was low over a 5-day period (Concha et al 2002).…”
Section: Biomarker Characterizationmentioning
confidence: 99%